ATMOSPHERIC DISTRIBUTIONS AND CHANGING TRENDS OF CFCS AND HALONS IN THE NORTHERN AND SOUTHERN HEMISPHERES - マキデ, ヨシヒロ; トミナガ, タケシ; MAKIDE, Yoshihiro; TOMINAGA, Takeshi (National Institute of Polar Research, 1994)
P(論文) Chlorofluorocarbons (CFCs), chlorocarbons, and bromofluorocarbons (Halons) with extremely long lifetimes are responsible not only for stratospheric ozone depletion but also for global warming. We have been accurately measuring atmospheric concentrations of those halocarbons (CFC-11,CFC-12,CFC-113,CFC-114,CH_3CCl_3,CCl_4,Halon-1301,Halon-1211,etc.) in the Southern Hemisphere (S.H.) as well as in the Northern Hemisphere (N.H.) in order to clarify the behaviors of these compounds in the atmosphere and to estimate the future trends of concentrations and their effects on the earth's environment. Surface level samples in Antarctica have been collected (since 1982) at 500-1000m NE (upwind direction) of Syowa Station (69°S) into all-stainless steel sample canisters which had been prepared in extremely clean conditions and evacuated for grab-sampling. All the Antarctic samples have been analyzed after 3-15 months at The University of Tokyo by ECD gas chromatography. Averaged concentrations in the mid-latitude N.H. have been obtained (since 1979) by analyzing the samples collected in Hokkaido (43-45°N) every summer and winter. Most samples collected in Antarctica have been stored in the laboratory for later measurement of new species and for checking the stability of calibration standards. Over the decade up to 1990,the averaged tropospheric concentrations of CFC-12 and CFC-11 observed in Antarctica were 9-10% lower than those observed in Hokkaido in accordance with the predominant emission of these CFCs in the N.H. and their delayed diffusion into the S.H. across the ITCZ, and the globally averaged concentrations of CFC-12 and CFC-11 increased almost linearly by about 4% a year. The concentration of CFC-113 in the S.H. was 20-30% lower than that in the N.H. and increased by 10-20% a year. However, since 1990,the increasing trends of major CFCs (CFC-12,CFC-11 and CFC-113) in the N.H. have changed drastically, slowing down to 0-3% a year. Their increasing trends in the S.H., on the other hand, have only slightly ...